Sports Stress in 21st Century: A Management Model in the Nigerian Situation - Emoghene, Blessing O. (International Journal of Human Kinetics, Health and Education, 2023)
Stress affects athletes’ life and performance, therefore understanding its many facets is crucial in sports. Nigerian athletes face a complex problem of sports stress in the 21st century. Athletes’ physical, mental, and performance are deeply affected by sports stress. This research examines sports stress in Nigeria and proposes a complete management plan. We suggest an integrated strategy to reduce sports-related stress based on Bronfenbrenner ecological system theory and many academic contributions. The Nigerian athlete-specific approach emphasizes cultural awareness and community support. It respects athletes’ varying cultural and linguistic origins and emphasizes the significance of knowing how stress is viewed and experienced differently. To equip athletes to manage stress holistically, the concept offers psychoeducation, family-centered techniques, and religious and cultural traditions. The approach also stresses the need of collaboration between athletes, coaches, support personnel, and the community to build social cohesion and resilience. It recognizes that athletes must be enabled to build personalized stress-reduction tactics that match their particular experiences. In Nigeria, sports stress management must be comprehensive and culturally appropriate. The suggested model acknowledges the intricate interaction of cultural, economic, and communal influences on athletes’ stress reactions by including Bronfenbrenner’s Ecological Systems Theory. It was concluded that Nigerian athletes need a comprehensive approach to physical, mental, emotional, and social well-being that addresses their particular demands and backgrounds. Hence, Coaches and support personnel require frequent cultural sensitivity training to better understand and meet Nigerian athletes’ unique demands.